Analisis Keterampilan Bercerita pada Siswa Kelas V SDN Kunciran 4 dalam Pembelajaran Bahasa Indonesia - Alfira Fazriandina; Yeni Nuraeni; Septy Nurfadhillah (FONDATIA, 2022)
Speaking skills by retelling have the aim of providing information by conveying expressions of feelings that are in accordance with the experiences experienced. The purpose of this study was to assess students' understanding of the level of creativity and concentration of students in storytelling, especially in retelling the story of the Formulation of the Proclamation Text. This research was conducted at SDN Kunciran 4 Tangerang City with the research subjects used as many as 15 students of class V elementary school category. The data collection technique used is descriptive qualitative research with the data collection process using observation, interviews and tests. Researchers looked at every practice carried out by students. The results of the analysis show that the skill level of the fifth grade students of SDN Kunciran 4 in learning Indonesian is quite good on several indicators. Based on the results of the analysis, it can be concluded that telling stories in front of the class can be mastered if students already have a sufficient level of confidence so that students will easily master themselves and tell stories carefully in front of the class.